Notice of Violation of IEEE Publication Principles: Design and Performance of an Off-Axis Free-Form Mirror for a Rear Mounted Augmented-Reality Head-Up Display System - Zhe An; Xiangping Meng; Xiu Ji; Xiping Xu; Yang Liu (IEEE Photonics Journal)
A novel optical-transmission rear mounted augmented reality head-up display, which can be used to improve the safety of a driving vehicle, is introduced and investigated in this paper. The proposed system uses an off-axis free-form mirror that serves as asymmetric aberration corrector. The off-axis aberration of the system is analyzed and the mirror is designed to correct both linear astigmatism and spherical aberration. This makes it possible to optimize the whole optical system. We also analyze the relationship between human eyes and the virtual image to obtain a registration matrix. The experimental results show that the size of the virtual image is 11 inches, the imaging distance is 2.8 meters, and the area of the eye box is 140 * 60 mm2. The novel system makes it possible to fuse the virtual image with the real-life scene to improve driver safety.